2004
DOI: 10.1111/j.1538-7836.2003.00525.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced leukocyte–platelet cross‐talk in Type 1 diabetes mellitus: relationship to microangiopathy

Abstract: Summary. Background: Platelets and leukocytes may in¯u-ence each others' function, i.e. platelet±leukocyte cross-talk. Diabetes mellitus (DM) is associated with platelet and leukocyte dysfunction. Objective: To evaluate platelet±leukocyte cross-talk, and if this might contribute to platelet and leukocyte dysfunction and microangiopathy in DM patients. Patients and methods: We evaluated platelet and leukocyte function, and cross-talk between these cells in Type 1 DM patients without (n 19) and with (n 20) micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 40 publications
2
40
0
2
Order By: Relevance
“…Previous studies have reported increased PLA formation in various clinical situations such as diabetic microangiopathy [15,29], acute myocardial infarction [14] and Raynaud’s phenomenon [16]. PLAs have been shown to be a more sensitive marker of platelet activation than platelet P-selectin expression [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported increased PLA formation in various clinical situations such as diabetic microangiopathy [15,29], acute myocardial infarction [14] and Raynaud’s phenomenon [16]. PLAs have been shown to be a more sensitive marker of platelet activation than platelet P-selectin expression [14].…”
Section: Discussionmentioning
confidence: 99%
“…Platelet-leukocyte aggregates (PLAs) are one of the important manifestations of these interactions. An increase in PLAs, which has been detected in coronary artery disease [14], diabetes [15] and autoimmune inflammatory diseases [13], has been suggested to participate in the pathogenesis of these diseases. In a recent report, systemic sclerosis patients with pulmonary hypertension were found to have higher numbers of PLAs [16].…”
Section: Introductionmentioning
confidence: 99%
“…fibrinogen binding) is augmented. [74,78,[82][83][84] Production of inflammatory cytokines, Figure 6. Mechanisms underlying increased clot formation in patients with diabetes.…”
Section: Aspirin: Antiplatelet Effects and Pharmacokineticsmentioning
confidence: 99%
“…iabetes is associated with platelet hyperactivity (1,2), increases in circulating activated platelets and platelet-leukocyte aggregates (PLAs), and platelet hyperreactivity to in vitro stimulation (2,3). Thromboxane-mediated platelet activation is of special interest since diabetes is associated with increased platelet-dependent thromboxane A 2 (TxA 2 ) production (2), and diabetic patients appear to benefit less from prevention with aspirin than nondiabetic patients (4,5).…”
mentioning
confidence: 99%